Blockchain Technology Prospect Study: an analysis from patent order documents - Brito, Samyr Leal da Costa (2020)
Blockchain technology has the potential to replace or complement existing practices related to the processing and validity of electronic data, and with application in several areas such as financial services, registration of tangible and intangible property, smart contracts, governance, among others. This article seeks to conduct technological prospection of this technology, based on the patent application documents found in the databases of Orbit, Espacenet and INPI (National Institute of Industrial Property). From the data collected, it was diagnosed that blockchain technology is not in an embryonic stage, but in the development and diffusion phase, given the significant number of patent documents published in the researched period.